Macrophage Migration Inhibitory Factor as a Biomarker of Severe Dengue and Shock in Children: A Cross-Sectional Study in Indonesia - Iskandar, Agustin; Korompot , Iswanto; Aprilia, Andrea; Ratri Dewi, Irene (Trends in Immunotherapy, 2026)
Dengue remains a leading cause of child mortality in Indonesia. Identifying reliable biomarkers to predict disease severity is essential for early intervention. Macrophage Migration Inhibitory Factor (MIF) is a pro-inflammatory cytokine involved in the pathogenesis of dengue. This study aimed to assess the relationship between MIF levels and dengue severity in children, and to compare the predictive value of MIF levels with C-Reactive Protein (CRP) and serum albumin levels. A cross-sectional study was conducted on 104 pediatric dengue patients hospitalized at Saiful Anwar General Hospital. Serum levels of MIF (ELISA), CRP, and albumin were measured upon admission. Patients were categorized into four severity grades (Grade 1–4) and also stratified into shock and non-shock groups. Statistical analyses included ANOVA, correlation analysis, and receiver operating characteristic (ROC) curve evaluation. MIF levels showed a significant stepwise increase with disease severity and were significantly higher in patients with shock (p < 0.001). CRP levels were also elevated in severe dengue, but the correlation with severity was moderate (r = 0.61, p < 0.05). In contrast, serum albumin levels were inversely associated with severity (r = –0.67, p < 0.05), with lower values observed in the shock group. ROC analysis demonstrated that MIF had the highest predictive accuracy for shock (AUC = 0.94), compared to CRP (AUC = 0.78) and albumin (AUC = 0.81). MIF is a robust biomarker for predicting dengue severity and shock in children, outperforming CRP and albumin in diagnostic performance. The integration of MIF with conventional markers may improve early risk stratification and clinical decision-making in pediatric dengue.